The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3389/ijph.2022.1605605
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Psychological Distress, Burnout and Work Engagement in Workers During the COVID-19 Pandemic: A Systematic Review

Abstract: Objective: The psychological distress that the COVID-19 pandemic has produced has generated negative effects on workers, and in one way or another this has affected their work engagement within companies. The aim of this research was to assess the relationship between psychological distress, burnout and work engagement in workers during the COVID-19 pandemic.Methods: A systematic review was carried out following the PRISMA methodology, taking articles from the Scopus, Pubmed, and Web of Science databases from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
(75 reference statements)
2
3
1
1
Order By: Relevance
“…In the latter country, it has been suggested that this effect on mental health could be due to fear of the collapse of the health system, with an increased workload that affected even areas outside those directly caring for the infected, and especially women because of the gender imbalance [ 47 ]. The higher percentage of PD among women is consistent with the findings of the present study and many others [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the latter country, it has been suggested that this effect on mental health could be due to fear of the collapse of the health system, with an increased workload that affected even areas outside those directly caring for the infected, and especially women because of the gender imbalance [ 47 ]. The higher percentage of PD among women is consistent with the findings of the present study and many others [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…It is known that the improvement of the work environment generates an increase in SOC and, with it, an improvement in the level of health is achieved [ 58 ]. A somewhat smaller association between work engagement and the level of PD has been found, which has also been reported in many other previous studies [ 26 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we investigated whether work engagement will change according to demographic and job characteristics in the post COVID-19 era. Although some studies have stated that variables such as age, gender, marital status, education, and work years were in uencing factors for work engagement, our research failed to fully established such relationship 35,38,39 . In our study, regression analysis showed that only gender was associated with absorption.…”
Section: Discussioncontrasting
confidence: 64%
“…The majority of participants in this study reported moderate and high levels of work engagement, with only a small proportion of employees exhibit low work engagement, similar to previous studies 2,18,33,34 . Although the COVID-19 has had a negative impact on the work engagement of healthcare workers, the impact is not obvious 35 . The possible reason is that the role played by healthcare workers in the epidemic has been highly recognized by society, and they feel a strong sense of belonging, good self-esteem, and self-ful llment, thereby improving or maintaining their work engagement.…”
Section: Discussionmentioning
confidence: 99%